Six lucid aspects of the staging of Luces de bohemia by Teatro del Temple in 2009 - Gracia Gaspar, Luis (Talía. Revista de estudios teatrales, 2023)
This article analyzes the staging of the play Luces de bohemia by the Teatro del Temple company in 2009. Its dramaturgical relevance contrasts with the scant academic attention received. We wanted to focus on six aspects of special interest in the staging itself: documentaries, narrative-scenic, spatial, aesthetic, interpretative and textual. Its analysis is particular because it is carried out from a recording, audiovisual peculiarity which links to those of the proposal to be studied, that shows that with a smaller number of actors and minimal scenographic elements the text can be carried out in all its splendor.